Pelatihan dan Pendampingan Mata Pelajaran Bahasa Inggris bagi Siswa-Siswi Sekolah Dasar Negeri Leyangan Terdampak Pandemi COVID-19 - Khusman Anhsori; Titis Handayani (Universitas Muhammadiyah Semarang, 2021)
Since the study from home system was implemented, several obstacles were found, especially for students at Elementary School of Leyangan in RT 004 RW 002 Dusun Krajan Desa Leyangan Kecamatan Ungaran Timur, Kabupaten Semarang. The students were difficult to learn the subjects by themselves, expecially for English subject. The main obstacles of study from home were lack of teacher’s direct explanation and lack of parents’ attention and mentoring. Based on this explanation, students needed face-to-face training and monitoring, especially the 'Self-Introduction' in English subjects. Through the USM’s Students Community Services Back to Village program, student focused on community service for face-to-face training and mentoring to improve the English skills for students at Elementary School of Leyangan. The community services method used was directly explanation and speaking practice for the given example sentences. The participants were required ro listen, rewrite and practice to speak for the given subjects. The mentoring was held in June 2021 with the COVID-19 health protocol face-to-face method. Evaluation results of the speaking pratice showed increment in students' knowledge and skill of 'Self-Introduction' subject and better pronunciation.